2014
DOI: 10.1515/pac-2013-1211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tetraazatetracenes and -pentacenes: role of the substituents for their stability

Abstract: We report the synthesis of a series of novel tetraazaacene derivatives and compare their stability with respect to size, oxidation potential and position of the TIPS-ethynyl groups. The latter has the most pronounced effects on the stability. In case of azatetracenes where TIPS-alkynes are either attached laterally or in the peri-positions, the former ones dimerized while the latter are stable. Attempts to expand this concept to the corresponding tetrakis-peri-substituted heptacenes led to the isolation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…7-Bromophenazine-2,3-diol (6). In a 250 mL round-bottom flask, 4-bromophenylenediamine (5.00 g, 26.7 mmol) and 2,5dihydroxy-p-benzoquinone (4.12 g, 29.4 mmol, 1.10 equiv) were dissolved in 150 mL of ethanol.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…7-Bromophenazine-2,3-diol (6). In a 250 mL round-bottom flask, 4-bromophenylenediamine (5.00 g, 26.7 mmol) and 2,5dihydroxy-p-benzoquinone (4.12 g, 29.4 mmol, 1.10 equiv) were dissolved in 150 mL of ethanol.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In the following years, a number of large azaacenes were prepared by many methods, and their properties were investigated by different spectroscopic methods and by electrochemistry. Azaacenes’ performance in organic electronic devices and their capability for singlet fission were investigated. , To further tune the azaacenes’ electrochemical properties, halogen atoms (F, Cl) were attached to their backbones. , Yet, with regard to potential applications as electroactive material, the parent, symmetrical bis­(triisopropyl­silyl­ethynyl)­tetra­azapenta­cene ( TIPS-TAP ) remains unchallenged in terms of stability and semiconductor performance.…”
Section: Introductionmentioning
confidence: 99%
“…Heteroacenes also have been reported to display good photoluminescence properties and high singlet fission cross‐sections, making them promising compounds for other applications [20–22] . In recent years, many azaacenes have been prepared by many methods, and their properties have been investigated by various spectroscopic methods and by electrochemistry [23–28] . The optical and electrochemical properties of N‐heteroacenes depend upon position and number of nitrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] In recent years, many azaacenes have been prepared by many methods, and their properties have been investigated by various spectroscopic methods and by electrochemistry. [23][24][25][26][27][28] The optical and electrochemical properties of N-heteroacenes depend upon position and number of nitrogen atoms. Miao and co-workers demonstrated that azaacenes containing nitrogens on internal rings exhibit lower FMO energies than their analogues with terminal heterocyclic rings.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many azapentacenes[ 28 , 29 , 30 ] and larger acenes[ 31 , 32 , 33 ] have been synthesized which are strong electron acceptors and exhibit n ‐semiconducting behavior. [ 3 , 4 , 5 , 6 , 14 , 17 , 18 , 34 , 35 ] These studies have revealed that the position of the nitrogen atoms in the aromatic core plays an important role in influencing the semiconducting properties, electronic structure and molecular packing.…”
Section: Introductionmentioning
confidence: 99%